Frosted branch angiitis associated with rapidly progressive glomerulonephritis. - Gupta Amod (Indian Journal of Ophthalmology, 2002)
Simultaneous occurrence of frosted branch angiitis and immune-mediated rapidly progressive glomerulonephritis is reported. The two diseases possibly share a common immune mechanism. Patients of frosted branch angiitis should undergo complete systemic evaluation including renal function tests even if the patient is systemically asymptomatic.